(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article provides a comprehensive analysis of the theoretical, methodological and practical aspects of improving the system of taxes levied on individuals and their role in ensuring the stability of state budget revenues. The study examines the evolution of mechanisms for taxation of individual income, stages of tax rate development, processes of digitalization of tax administration and their impact on tax revenues. The article summarizes in a systematic manner scientific views on improving the system of tax collection from individuals based on the experience of Europe, the USA, Asia and the CIS countries. In particular, the issues of automated declaration systems, real-time income monitoring, risk models based on artificial intelligence, optimization of tax benefits and expansion of the tax base are analyzed in depth. The article develops practical proposals for creating an integrated electronic register that fully covers the income of individuals, establishing automatic information exchange between banks, employers and government agencies, widely introducing an automatic tax reporting system, strengthening intellectual tax control based on risk models, targeted revision of tax benefits, fully launching a digital register of labor contracts, and developing "personal tax office" services. It is argued that these measures will serve to increase the stability of budget revenues from individual taxes, reduce the share of the shadow economy, and improve the culture of paying taxes.